Study Of Motion Estimation Algorithms For Interpolation Of Low Rate Video Frames - Abdul Karim, Hezerul (2002)
It is a great challenge to interpolate low rate video frames when the movement is large. Using classical block matching methods introduces a combinatorial explosion problem. In this thesis, the 5-to-10 frames per second(fps) interpolation problem is considered, with view on videoconferencing application. Several methods are investigated, from plain averaging, over block matching methods, up to multi-resolution approaches.